Pengaruh Motivasi dan Dukungan Sosial terhadap Self Efficacy Mahasiswa dalam Mengikuti Pendidikan Teologi di Fakultas Teologi -UKIM - Claartje Pattinama (JTP - Jurnal Teknologi Pendidikan, 2020)
This study aims to measure the effect of motivation and social support on students self-efficacy in attending theological education. This research is a quantitative study, with research subjects being students of the Theology Faculty - UKIM. Data analysis was performed using Structural Equation Model (SEM). The results showed that: Motivation with indicators of intellectual knowledge and parental expectations for students had a positive and significant effect on students self efficacy in attending Theological education, as well as social support with information indicators and emotional support had a positive and significant direct effect on self efficacy in students. This concludes that there is a positive and significant influence between motivation and social support on students' self-efficacy in attending theological education at the Theology Faculty of the Indonesian Christian University of Maluku in the hope that when they graduate they will be able to develop their theological education as pastors in the congregation and teachers of Christian Religious Education and in school.